THE COMPARISON BETWEEN STRUCTURAL PARTICLE “?” IN MANDARIN AND STRUCTURAL PARTICLE “DENGAN” ATAU “SECARA” IN INDONESIAN - Septevany, Elvira; Dandan, Liu; Weifen, Qin; Xing, Lu (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2021)
The uses of structural particle “? dengan/secara” in Mandarin or in Indonesian have similarities and differences. In order to compare these two words, the writer uses contrastive analysis which is a study to identify the differences and similarities between Indonesian and Mandarin structural particle. The data collection technique was done by using purposive sampling technique. It was taken randomly from Modern Indonesian books and then compared with structural particle in Mandarin. The result of this analysis is that there are similarities and differences in the use of the structural particle “? de” in Mandarin and “dengan” or “secara” in Indonesian. Besides, there are also differences in word usage. The difference can be seen from the uses of structural particle “? de” in Mandarin and the structural particle “dengan” or “secara” in Indonesian in other words. The “?” marker in Mandarin can only corresponds to the adjective word class while the Indonesian language is more flexible because the structural particle “dengan” or “secara” can match the adjective, verb, noun, or adverb word class. The structural particle “dengan” or “secara” when corresponding to the word class will indicate a method, style or manner of doing something.